IMPLEMENTASI KERJASAMA PROGRAM STUDI AGROBISNIS POLITEKNIK NEGERI SAMBAS DENGAN PT WILMAR GROUP KALIMANTAN BARAT - Dian Diana; Sukmawati Sukmawati; Usman Radiana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis reseach aims to determine the implementation of the Agribusiness Study Program collaboration with PT Wilmar Group in West Kalimantan, especially at PT Agronusa Investama Wilmar International Plantation West Kalimantan. The research method uses a qualitative research approach with data collection techniques such as observation, interviews and document studies. Analysis of the data in this study are (1) data reduction, (2) data display (3) conclusions. Subyck of research consisted of 7 people, consisting of 4 men, 3 women, aged from 20 to 52 years, and the lowest educated, high school one person, D-III two people, SI one person and S2, 3 people. The data source of this research is the results of interviews,research data were obtained from document studies and observations. The results showed that the mutually beneficial cooperation was planned well so that the implementation of the collaboration proceeded smoothly in accordance with the targets set. Equivalent cooperation is also going well while responsible cooperation is going well enough. This collaboration should produce competent human resources in the plantation sector. The implication is shown by the alumni recruitment of Sambas State Polytechnic Study Program at PT Wilmar, especially at PT Agronusa Investama Wilmar International Plantation Sambas, West Kalimantan.Key words: Agribusiness, Cooperation, Implementation.